PENGARUH EKSTRAKURIKULER PRAMUKA TERHADAP PENGUATAN CIVIC DISPOSITION DI MTs DARUL HIKMAH PEKANBARU - Zahrah Gita Ananda; Hambali Hambali; Supentri Supentri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research is motivated by efforts to improve character education and the desire to build students' civic character which is increasingly important in line with the phenomenon of moral degradation which often occurs among students who do not reflect their civic character. For this reason, efforts are needed to perfect civic character (civic disposition) which can not only be done through PPKn learning, but can also be done through extracurricular scout activities. The aim of this research is to find out whether there is a positive influence of scouting extracurricular activities on strengthening civic disposition at MTs Darul Hikmah Pekanbaru. This research method is quantitative with a statistical approach. The population in this study was all students who took part in special scouting extracurriculars, consisting of 40 students, consisting of class VII and class VIII. The sample in this research is the entire population or also called total sampling. Data analysis in this study used the normality test, linearity test, simple linear regression test, coefficient test (R) and correlation of determination (R-square), and hypothesis testing. The hypothesis in this study was accepted, which showed Fcount ≥ Ftable (14.933 ≥ 4.098) and the results of this study showed that Scout Extracurriculars had a Positive Influence on strengthening Civic Disposition at MTs Darul Hikmah Pekanbaru. This can be seen from the results of calculating the coefficient of determination (R-square) of 0.517, which means that scout extracurricular activities (independent variable) have an influence on strengthening civic disposition (dependent variable) by 51.7%, while 48.3% is influenced by other variables. not examined in this study.